A novel motif in the 5'‐UTR of an orphan gene 'Big Root Biomass' modulates root biomass in sesame. Issue 5 (1st February 2021) - Dossa, Komivi; Zhou, Rong; Li, Donghua; Liu, Aili; Qin, Lu; Mmadi, Marie A.; Su, Ruqi; Zhang, Yujuan; Wang, Jianqiang; Gao, Yuan; Zhang, Xiurong; You, Jun
Summary: Developing crops with improved root system is crucial in current global warming scenario. Underexploited crops are valuable reservoirs of unique genes that can be harnessed for the improvement of major crops. In this study, we performed genome‐wide association studies on seven root traits in sesame ( Sesamum indicum L.) and uncovered 409 significant signals, 19 quantitative trait loci containing 32 candidate genes. A peak SNP significantly associated with root number and root dry weight traits was located in the promoter of the gene named ' Big Root Biomass ' ( BRB ), which was subsequently validated in a bi‐parental population. BRB has no functional annotation and is restricted to the Lamiales order. We detected the presence of a novel motif 'AACACACAC' located in the 5'‐UTR of BRB in single and duplicated copy in accessions with high and small root biomass, respectively. A strong expression level of BRB was negatively correlated with high root biomass, and this was attributed to the gene SiMYB181 which represses the activity of BRB by binding specifically to the single motif but not to the duplicated one. Curiously, the allele that enhanced BRB expression has been intensively selected by modern breeding. Overexpression of BRB in Arabidopsis modulates auxin pathway leading to reduced root biomass, improved yield parameters under normal growth conditions and increased drought stress sensitivity. Overall, BRB represents a solid gene model for improving the performance of sesame and other crops.